Mass Regimes: Geometric Actuation of Thermal Behavior. (June 2015) - Cupkova, Dana; Azel, Nicolas
The Mass Regimes is a research project that investigates the effect of complex geometry on processes of passive heat distribution in thermal mass systems. In the context of systems thinking, this research intends to instrumentalize design principles that engage a wider range of design tactics for choreographing thermal gradients between buildings and their environment. Research for this project has brought about a deeper understanding of how specific geometric manipulations of surface area over the same mass (Figure 1) affect the rate of thermal transfer. Leveraging physical simulations of geometric populations, along with current computational and design tools, the project sheds light on performative trends that may enhance creative design explorations in the use of passive systems. Preliminary analysis of varied geometric populations suggest an exciting trend and the possibility for a more synthetic incorporation of morphology, one in which surface geometry can be passively utilized to generate effects with more fidelity over the pace of thermal absorption and the release of sensible heat.